TRANSFORMASI PARADIGMA HUKUM PERTANAHAN DI INDONESIA: DARI PENDEKATAN REPRESIF MENUJU PARTISIPATIF - Rendy Renaldy (Jurnal Perspektif Hukum, 2025)
The paradigm of land law in Indonesia faces significant challenges due to the dominance of a repressive approach in land management and control by the state. This approach often disregards community participation and the rights of indigenous peoples, leading to prolonged agrarian conflicts. This study aims to analyze the transformation of land law from a repressive approach to a more participatory and just legal framework. The research employs a normative juridical method combined with historical and sociological approaches, analyzing legislation, legal documents, and case studies of agrarian conflicts. The findings indicate that transforming land law requires structural and institutional changes, recognition of indigenous collective rights, and active community involvement in all stages of land policy. This paradigm shift is essential in developing a democratic, transparent, and community-oriented land law system.